Design of Round-Nozzle Inertial Impactors Review with Updated Design Parameters - Francisco J. Romay; Estíbaliz García-Ruiz (Aerosol and Air Quality Research)
Abstract Round-nozzle inertial impactors are widely used aerosol measuring instruments to characterize the mass and chemical composition of airborne aerosol particles as a function particle aerodynamic diameter. This article summarizes the most important design considerations with updated recommended design parameters taken from our review of published research articles and discusses some of the more common non-idealities seen in the operation and performance of inertial impactors. With this information, it is now possible to design a cascade impactor with near-ideal particle separation performance, and with stage cutpoints that can be predicted with excellent accuracy and verified experimentally using state-of-the-art calibration techniques.